Sternotomy and Pericardiectomy in a Patient with Constrictive Pericarditis and Multiple Comorbidities: A Case Report - Dedy Chandra Hariyono; Prima Kharisma Hayuningrat (HM Publisher, 2025)
Background: Constrictive pericarditis is a serious condition that can lead to heart failure. It is characterized by a thickened and scarred pericardium, which restricts the heart's ability to fill and pump blood effectively. The condition is often caused by infections, such as tuberculosis, but can also be caused by other factors, such as radiation therapy, heart surgery, or autoimmune diseases. A pericardiectomy, a surgical procedure to remove the thickened pericardium, is the definitive treatment for constrictive pericarditis. Case presentation: This case report describes a 57-year-old male patient with constrictive pericarditis and multiple comorbidities, including recent tuberculosis, pleural effusion, ascites, and cholelithiasis. The patient presented with symptoms of shortness of breath, swollen legs, and a swollen stomach. After a thorough evaluation, including imaging studies, the diagnosis of constrictive pericarditis was confirmed. The patient underwent a sternotomy and pericardiectomy procedure, which was successful in relieving his symptoms and improving his cardiac function. Conclusion: This case report highlights the successful management of constrictive pericarditis in a patient with multiple comorbidities. The case also emphasizes the importance of early diagnosis and timely intervention in patients with constrictive pericarditis.